Synthesis, Chemical Characterization and Antibacterial Activity of Some Novel Triazole Substituted 5-Oxo-Imidazoline Derivatives - Yerra, Rajeshwar (Journal of Tropical Pharmacy and Chemistry, 2024)
5-oxo-imidazoline rings have been reported to possess various biological activities such as antibacterial, anticancer, antifungal, and anthelmintic activities. These activities also include anticonvulsant, and anthelmintic.   These observations and findings prompted to synthesize the novel triazolo substituted 5-oxo-imidazoline derivatives.  In the present investigation, a series of 10 new 1-trazolyl-5-oxo-imidazolinones were synthesized in good yield by using appropriate synthetic methods and have been established on the basis of their M.P., TLC, FT-IR, 1H-NMR, 13C-NMR data.  Also, all the compounds were evaluated for the possible antibacterial activity by cup-plate agar diffusion method by measuring % zone of inhibition.  Streptomycin at the concentration of 50?g/ml was used as standard drug.  Of all the tested compounds, A6 exhibited significantly high potency against the various gram positive and gram negative organisms used in the investigation.